Expedition of Thirst : Exploring Breweries, Wineries, and Distilleries across the Heart of Kansas and Missouri - Dulin, Pete (Book collections on Project MUSE., 2017)
"In Expedition of Thirst, KC-based food writer Pete Dulin explores 151 breweries, wineries, and distilleries across central Kansas and Missouri, from Hays in the west to Columbia in the east. This guidebook will be the first to look at all three types of local alcohol producers in the bi-state region, and the first to cover so much area, as most existing products only focus on Kansas City. Dulin structures the book along highways, guiding readers by the routes they would follow rather than by geographic zones or type of production. An introduction gives background on the history and culture of drinking in the region, particularly the ways major forces like Prohibition, transportation, and state laws impacted alcohol production and use. Entries provide the basic information expected in a guidebook, but also tell the stories of these venues and the people who run them. Readers will gain insight into how local history and conditions--such as ethnic brewing traditions, agricultural products, and politics--impact the beverages each company produces. Intended for residents and visitors alike, Expedition of Thirst will inspire readers to explore this growing industry and sample the history, terroir, and skill of regional vintners, brewers, and distillers"--Provided by publisher